Research on the Relationship between Earnings Management and Corporate Governance: Data from Chinese Pharmaceutical Industry - Yan, Xin-Yu (2019)
The main objective of this research is to find the correlation between earnings management and corporate governance element by conducting regression analysis on data from sample companies of Chinese pharmaceutical industry over the five-year period from 2014 to 2018. According to previous literature, discretionary accruals is used as dependent variable, measured by modified Jones model. Seven typical independent variables are used to reflect corporate governance, namely shareholding ratio of the first majority shareholder and management shareholding ratio, representing capital structure; board size, board independence and board meeting times, representing board characteristics; CEO duality and executive compensation, representing management characteristics. Furthermore, three control variables namely firm size, ROE and leverage ratio are also included to increase the stability of regression. As shown clearly in the result of random effect regression model which is adjusted by robust standard error, shareholding ratio of the first majority shareholder and executive compensation have significantly negative correlation with earnings management, while board meeting times has significantly positive correlation with earnings management. As for the remaining independent variables, there does not exist clear evidence to support that they have certain impact on earnings management.